2019
DOI: 10.1007/s10964-019-00988-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stressful Parenting and Mineralocorticoid Receptor Haplotypes on Social Development During Adolescence and Young Adulthood

Abstract: The development of social behavior could be affected by stressful parenting. The mineralocorticoid receptor, one of the two main receptors for the stress hormone cortisol, plays a vital role in adequate responses to stress. Therefore, the effects of stressful parenting on social development (i.e., empathic concern, perspective taking and prosocial behavior) may be moderated by functional genetic variation in mineralocorticoid receptor haplotypes (a combination of alleles). A group of 343 adolescents (44.3% fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
(111 reference statements)
1
1
0
Order By: Relevance
“…There were no significant interaction effects between stressors and MR CA haplotype, suggesting that MR CA haplotype is equally protective in low and high stressful environments. However, a study in the same sample showed a positive effect of MR CA haplotype on prosocial behavior, empathic concern and perspective taking for adolescents who experienced high levels of stressors, and negative effects for adolescents who reported low levels of stressors (41). Such a protective effect of MR CA haplotype under circumstances of high stress is in line with the study of Vinkers et al (11) that found stronger MR CA haplotype effects for higher levels of childhood trauma.…”
Section: Discussionsupporting
confidence: 69%
“…There were no significant interaction effects between stressors and MR CA haplotype, suggesting that MR CA haplotype is equally protective in low and high stressful environments. However, a study in the same sample showed a positive effect of MR CA haplotype on prosocial behavior, empathic concern and perspective taking for adolescents who experienced high levels of stressors, and negative effects for adolescents who reported low levels of stressors (41). Such a protective effect of MR CA haplotype under circumstances of high stress is in line with the study of Vinkers et al (11) that found stronger MR CA haplotype effects for higher levels of childhood trauma.…”
Section: Discussionsupporting
confidence: 69%
“…Interactions with parents also provide a safe space to learn conflict-resolution skills, as relationships with parents can be used as a model for later relationships with peers (Van Lissa et al, 2016). Adolescents who are unable to have these learning experiences, for example due to parental maltreatment, show slower development of perspective-taking abilities (Endedijk et al, 2019). Multiple studies reveal the importance of perspective taking in successfully navigating parent-child conflict, as adolescents with higher levels of perspective taking show more interest in their mother's thoughts during a conflict discussion (Lougheed et al, 2020) as well increased sensitivity in adapting their behavior to their mother's responses (Disla et al, 2019).…”
Section: Parentsmentioning
confidence: 99%